The Laba Per Saham, Rasio Hutang, Pengembalian Atas Aset dan Suku Bunga Terhadap Nilai Perusahaan Wholesale - Elise Elise; Mariska Sisilia; Rina Yustito S; Cherria Halim (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine the effect of earnings per share, debt ratio, return on assets and interest rates on firm value in whosale companies listed on the IDX in 2014-2018. This research was conducted using an associative research method and a quantitative approach. 17 companies as samples were taken using purposive sampling method. The analysis model uses multiple linear regression equations. The result of the research is that earning per share has no effect on firm value at Whosale companies listed on the IDX. The debt ratio does not affect the firm value of Whosale companies listed on the IDX. Returns on assets have an effect on firm value at Whosale companies listed on the IDX. Interest rates do not affect the firm value of Whosale companies listed on the IDX. Earnings per share, debt ratio, return on assets and interest rates have an effect on firm value at Whosale companies listed on the IDX.